"I just don't feel like myself anymore": putting the patient's voice into integrated care. (14th September 2018) - Ferguson, Shelagh
Abstract : Purpose: This paper aims to elucidate health-related transformations experienced by an individual. Building from personal experience offers an understanding of the relational dynamics at play within health transformations, which makes a contribution to realising and facilitating the agency of the patient in systems of integrated care. Design/methodology/approach: Introspection can be used as a methodology to elucidate messy and personal affective experiences. The author's introspection is an 18-month catalogue and analysis from diagnosis of breast cancer through significant stages of rehabilitation. Reflexive introspection has gained traction in health research due to its cathartic benefits, whilst this approach offers much; a key challenge for integrated care is translating deeply personal and subjective introspections into strategic-level application. Findings: Using Turner's (1969) concept of liminality, this research explicates key relational dynamics of health-related transformations experienced by an individual. By recognising changes in affective being as a pivotal point in rehabilitation, this work links embodied transformation as a critical antecedent to a patient's willingness to engage his/her agency in their rehabilitation. Originality/value: Whilst recognising that integrated care is patient-centred and seeks to incorporate the patient's voice, this research gives insight into how the author, as a patient, engaged her agency in her rehabilitation through building her own transformed personal ontologies of health.